1990
DOI: 10.1038/ki.1990.20
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur amino acid metabolism in cystinuria: A biochemical and clinical study of patients

Abstract: Sulfur amino acid metabolism was studied in 26 homozygotic cystinuric patients, some of whom received D-penicillamine, 2-mercaptopropionylglycine or N-acetylcysteine treatments in order to evaluate signs of cyst(e)ine deficiency. Decreased leukocyte glutathione and taurine levels, plasma cyst(e)ine and taurine concentrations and urinary inorganic sulfate, taurine, mercaptolactate and thiosulfate outputs were found in cystinuric patients, probably reflecting intracellular cyst(e)ine deficiency. An increased mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…That ascorbate protects against experimental GSH deficiency suggests that it may be useful in treating patients with inborn deficiencies of y-glutamylcysteine and GSH synthetases (66), premature newborns, and others deficient in GSH (67)(68)(69). Although ascorbate can induce oxidative stress (see ref.…”
Section: Resultsmentioning
confidence: 99%
“…That ascorbate protects against experimental GSH deficiency suggests that it may be useful in treating patients with inborn deficiencies of y-glutamylcysteine and GSH synthetases (66), premature newborns, and others deficient in GSH (67)(68)(69). Although ascorbate can induce oxidative stress (see ref.…”
Section: Resultsmentioning
confidence: 99%
“…The brush border mem brane transport is dependent on sodium and may possibly occur at the same site as cysteine. Our research group has noted previously that the sulfhydryl compounds Z)-penicillamine and tiopronin exert their effects in cystinuria not only by the formation of a mixed disulfide in urine, but probably also by promoting an increased intracellular cystine metabolism [29]. It has also been reported that the sulfhydryl compound mercaptoethanol might improve the intracellular utilization of cystine by facilitating the transport of cystine into the cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…The presence or a sulfhydryl compound, 2-mercaptoethanol, improves the cellular uptake of cysteine in leuko cytes by facilitating the transport across the cellular mem branes [29], In a study of the biochemical effects of some sulfhydryl compounds in cystinuria we found signs of nor malization of cystine metabolism following administra tion of tiopronin and D-penicillamine [30], These results indicate that a change in the general metabolism of cys tine and cysteine induced by tiopronin may contribute to the dose-related decrease in urinary excretion of the total cystine observed in our patients.…”
Section: Total Urinary Excretion O F Cystine As Free Cystine and Mixementioning
confidence: 99%